PENGARUH RASIO KEUANGAN DAN EKONOMI MAKRO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA - ., Nurdina (MALIA (TERAKREDITASI), 2017)
Capital markets can be interpreted as a container for investors to run investments in financial assets. Investing in the stock market can be in the form of bond holdings, stocks, mutual funds, and other financial instruments. The companys short-term goal is not just to get the most profit. The increase in profits has an impact on the rising value of the firm, which means giving an indication of shareholder prosperity is also increasing.Corporate value can be measured not only by stock prices, but can use price to book value (PBV). The values reflected through PBV are influenced by several factors such as the firms fundamental conditions and inflation.The purpose of this study is to examine the effect of financial ratios and macroeconomic on the value of the company on shares of automotive companies and its components in the Indonesia StockExchange.The variables used are Debt to Equity Ratio (DER), Return on Assets (ROA), and inflation. The type of research is comparative causal. The population is all the automotive companies listed on the Indonesia Stock Exchange as many as 13 companies during the year 2014-2016. This research uses purposive sampling method, Data Analysis using SPSS 20.The statistical results show ROA effect on Price to Book Value, while DER and inflation did not affect the Price to Book Value.